PEMBUNGAAN DAN PRODUKSI TANAMAN JAGUNG DI LAHAN PASIR - B. Suwignyo; B.W. Pratomo; Nonok Supartini; N. Umami; B. Suhartanto (Universitas Tribhuwana Tunggadewi, 2012)
The study aimed to determine fowering and production of corn planted in sandy soil. The study is based on completely randomized design (CRD) with three replications in Jangkaran Village, Temon, Kulonprogo, Yogyakarta The data were analyzed by ANOVA with SPSS advanced analysis of LSD. Treatments were plastic and bio mulch (feedstuff used), and planted with Pioneer® seed corn. Plant spacing was 25 x 50 cm. Litter manure waste was used as basal fertilizer by spreaded over the beds at the level 7.5 t/ha. Chemical fertilizers, Urea and SP-36 are given and water irrigation each day. Number of flower was observed since the first time of flowering up to harvested (10 weeks). Production was determined from total weight of whole plant harvested. Corn plant with bio mulch produced significantly higher number of flower and total whole plant compare with control but not significantly with plastic mulch. Bio mulch always has highest number of flower 34.4% compare with plastic mulch 17.7% and control 9.2. The highest production level of fresh whole plant 13.3, plastic mulch 12.93 and 3.91 t/ha